PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI POKAMATHH (POWER POINT KAHOOT MATEMATIKA) MATERI ALJABAR KELAS VII SMP IT DOD MEDAN - Ilham Nazaruddin; Ronald Mahmud S; Mardianto Mardianto; Satria Ami Marta; Bayu Samudra; Ery Novita Sari (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
The objective of creating this POKAMATH media is to evaluate the effectiveness and usability of educational media employing the ADDIE framework, which includes: (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evaluation. The inspiration for this study stems from the students' lack of concentration during classroom instruction when the teacher presents material. The media's validity was assessed by three different validators: experts in media, subject matter, and language. To evaluate its practicality, student feedback surveys were administered, with participants being pupils from SMP IT DOD Medan selected through simple random sampling methods. The overall score from the validity review, covering content, media, and language, reached a perfect score of 100%, categorizing it as highly valid. Meanwhile, the practicality evaluation in a smaller class setting yielded a score of 90%, placing it in the very practical category. Consequently, the POKAMATH media developed is both valid and suitable for seventh-grade students at SMP IT DOD Medan.